2013
DOI: 10.1556/jba.2.2013.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesizing repetitive paraphilia behavior of a medication refractive Tourette's syndrome patient having rapid clinical attenuation with KB220Z-nutrigenomic amino-acid therapy (NAAT)

Abstract: Background and aims:Many patients presenting multiple behaviors including drug and food abuse as well as other pathological repetitive unwanted activities such as gambling, self-mutilation and paraphilias may not be appropriately diagnosed. Here we present a case of a male presenting many of these seemingly diverse behaviors and finally diagnosed with reward deficiency syndrome (RDS) by his attending physician. Methods: The use of the dopamine agonist, ropinirole after two weeks showed improvement in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…There is also evidence of reduced craving for alcohol, heroin, cocaine, and nicotine. Also, reductions in inappropriate sexual behavior and reduced post-traumatic stress (PTSD) symptoms such as paraphilia have been reported ( McLaughlin et al, 2013 ). Quantitative electroencephalography (qEEG) studies in humans have found that KB220Z modulates theta power in anterior cingulate cortex.…”
Section: Is There a Solution To Rds?mentioning
confidence: 99%
“…There is also evidence of reduced craving for alcohol, heroin, cocaine, and nicotine. Also, reductions in inappropriate sexual behavior and reduced post-traumatic stress (PTSD) symptoms such as paraphilia have been reported ( McLaughlin et al, 2013 ). Quantitative electroencephalography (qEEG) studies in humans have found that KB220Z modulates theta power in anterior cingulate cortex.…”
Section: Is There a Solution To Rds?mentioning
confidence: 99%
“…Can we overcome DNA polymorphisms by promoting positive epigenetic effects which can be transferred from generation to generation [57]? With this in mind we wonder if we have been "licking our pups" enough, so that we could potentially attenuate substance and non-substance seeking-behaviors through love-understanding that "love needs care" [58,59].…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence of reduced craving for alcohol, heroin, cocaine, and nicotine. Also, reductions in inappropriate sexual behavior and reduced posttraumatic stress disorder (PTSD) symptoms such as paraphilia have been reported (McLaughlin et al 2013). Quantitative electroencephalographic (qEEG) studies in humans have found that KB220Z modulates theta power in the anterior cingulate cortex.…”
Section: Dopamine Agonist Therapy: Reasons For Blocking Rewardmentioning
confidence: 99%